Social-Cultural Processes and Urban Affordances for Healthy and Sustainable Food Consumption - Carrus, Giuseppe; Pirchio, Sabine; Mastandrea, Stefano (Frontiers in Psychology, 2018)
In this paper, we provide an overview of research highlighting the relation between cultural processes, social norms, and food choices, discussing the implication of these findings for the promotion of more sustainable lifestyles. Our aim is to outline how environmental psychological research on urban affordances, through the specific concepts of restorative environments and walkability, could complement these findings to better understand human health, wellbeing and quality of life. We highlight how social norms and cultural processes are linked to food choices, and we discuss the possible health-related outcomes of cultural differences in food practices, their relation to acculturation and globalization processes. We also discuss the concepts of restorative environments and walkability as positive urban affordances, and their relation to human well being, and the possibile link with cultural process and sustainable lifestyles. Finally, we outline issues for future research and areas for policy making and interventions on the links between cultural processes, healthy and sustainable food consumption and urban affordances, for the pursuit of public health, wellbeing and environmental sustainability.